Sotaharjoituksen aiheuttamat muutokset autonomisen hermoston toiminnassa, hormonaalisissa ja aineenvaihdunnallisissa vasteissa, sekä koetussa rasittuneisuudessa - Seppänen, Juho (2024)
Stress causes changes in the body in the functioning of the autonomic nervous system and in hormonal and metabolic systems. Factors that cause stress in military field training are, for example, individual factors, physical strain, cognitive tasks, environmental factors, lack of sleep, energy deficit and psychological factors. The aim of this study was to investigate the stress caused by military field training measured by heart rate variability, hormonal and metabolic variables and perceived exertion. In addition, the purpose was to find out how the changes were connected to each other, and whether endurance fitness and body composition were related to the changes. 49 men (age 20 ± 1 years; height 179,1 ± 7,2 cm; weight 73,0 ± 8,8 kg) participated in the study. The research period consisted of a three-week military exercise, which was divided into a shooting training period (5 days), a first combat training period (8 days) and a second combat training period (7 days). Subjects' nocturnal and morning heart rate variability, hormonal and metabolic variables, physical activity, perceived exertion, and amount of sleep were measured before the military field training, periodically during the training, and 4–5 days after the end of the military field training. During the three-week military field training, nocturnal and morning heart rate, cortisol, SHBG, CK, RPE and NASA-TLX increased (p < 0.05). On the other hand, testosterone, TES/COR and IGF-1 decreased (p < 0.05). Only a few statistically significant changes were observed in heart rate variability variables. The observed stress caused by the military field training seems to recover to its initial levels or close to them within 4–5 days after the end of the training. There were weak associations between the changes in many measured variables, and rarely clear associations. RPE was associated with testosterone (r = –0.30, p < 0.05) and NASA-TLX with cortisol (r = 0.49, p < 0.01). The associations of aerobic fitness and body composition to the changes of heart rate variability, hormonal and metabolic adaptations, and perceived exertion were unclear. The stress caused by military field training caused changes in the functions of the autonomic nervous system, hormonal and metabolic systems, and in perceived exertion. The changes indicate that the training increased the subjects' physiological and/or psychological stress leading the body to a more catabolic and overreaching state. It was challenging to interpret the results because the changes varied individually. The present study can provide interesting data about the workload of military field training. Especially poor quality heart rate data caused challenges to the study. Different measurement methods and tools, and standardization are needed for obtaining better quality data and thus, improving the reliability and reproducibility of the study. Finally, individual responses and adaptations should be taken into consideration.